If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + -3x = 40 + -5x Solving -16 + -3x = 40 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -16 + -3x + 5x = 40 + -5x + 5x Combine like terms: -3x + 5x = 2x -16 + 2x = 40 + -5x + 5x Combine like terms: -5x + 5x = 0 -16 + 2x = 40 + 0 -16 + 2x = 40 Add '16' to each side of the equation. -16 + 16 + 2x = 40 + 16 Combine like terms: -16 + 16 = 0 0 + 2x = 40 + 16 2x = 40 + 16 Combine like terms: 40 + 16 = 56 2x = 56 Divide each side by '2'. x = 28 Simplifying x = 28
| 5u(u+9)(u-6)=0 | | 6z-4z+2z= | | 6(u+2)=48 | | (-x-6)-(2x+5)= | | x+12+9x=40 | | X^3-2(2+6)=0 | | 3(n-3)=-42 | | 150(225+3.5x)=2000 | | 3x^2+2y=o | | 4(6m+7)+2(3m-6)= | | 12-15y=4 | | x^8-2x^4+1= | | 4W+28=16v | | 25x^2+100x+200=0 | | 3(x+12)=3x | | 17x-5=80 | | K^2=200 | | 4x+20=2(3x) | | A=3x+6 | | 5n+4-8h=-5 | | -4(m-6)=-48 | | -9-7n=-5 | | -3(-2g+16)= | | .75x-.33x=9 | | -2(-8+3c)= | | 3(g+3)=24 | | 3(10)-5y=20 | | (5u-3)(4+u)=0 | | 7-2(-5x-9)+2x=4(2x-1)+3x+2 | | -11(16-13z)= | | 9-9r=-8 | | 15+3z=39 |